The in vitro diagnostics industry in China. Issue 1 (23rd March 2020) - Song, Haibo; Zhu, Yaoyi
Abstract: In vitro diagnosis refers to the diagnosis of diseases or other condition of the human body through the collection, preparation, and testing of human samples with reagents, instruments, and systems. The purpose of in vitro diagnostics is to provide information for the alleviation, treatment, and prevention of diseases and their complications. Enterprises engaged in the production, development, marketing, service, and application of in vitro diagnostic instruments, reagents, standards, consumables, and quality‐control products constitute the in vitro diagnostic industry. China's in vitro diagnostic industry began in the 1980s and has developed rapidly, from simple products to large systems and from single products to complete industrial chains. In vitro diagnostics has become the world's second‐largest sales market and second‐largest production base. Looking to the future, China's in vitro diagnostics industry is projected to maintain a growth rate more than double that of the global market and contribute to the development of Chinese and the global industry.